Invasive and Noninvasive Assessment of Exercise-induced Ischemic Diastolic Response Using Pressure Transducers - Manolas, Jan (Current Cardiology Reviews, 2015)
Left ventricular (LV) pressure curve shows early high-magnitude changes in the presence of induced ischemia. A dramatic rise in LV and left atrial end-diastolic pressures occurs within seconds to minutes in the presence of ischemia induced by dynamic or handgrip exercise as well as pacing of 38 to 183% and during short coronary balloon occlusion of 32 to 208% of baseline. Changes in relaxation or volumetric filling rate or ejection fraction were significantly less pronounced. Similar end-diastolic abnormalities occurring mainly in patients with coronary artery disease (CAD) have been shown in noninvasive recordings obtained by pressure transducer placed over the point of maximal LV beat (pressocardiograms). Specifically, the amplitude of the A wave to total excursion of pressocardiogram showed a similar high-magnitude increase after dynamic or handgrip exercise in average by 60 to 142% of baseline; however, changes in pressocardiographic relaxation time indexes were only slightly abnormal. A well-defined “ischemic pattern” of pressocardiographic diastolic changes with handgrip, showed a high prevalence in CAD patients. The assessment of diastolic changes in the presence of handgrip-inducible ischemia using noninvasive pressure transducers might provide after further studies a simple complementary diagnostic tool to assist in identification of patients with atypical or asymptomatic CAD.
Keywords: end-diastolic pressure